Cyclosporine versus tacrolimus: cost-effectiveness analysis for renal transplantation in Brazil - Guerra Júnior, Augusto Afonso; Silva, Grazielle Dias; Andrade, Eli Iola Gurgel; Cherchiglia, Mariângela Leal; Costa, Juliana de Oliveira; Almeida, Alessandra Maciel; Acurcio, Francisco de Assis (Revista de Saúde Pública, 2015)
OBJECTIVE To analyze the cost-effectiveness of treatment regimens with cyclosporine or tacrolimus, five years after renal transplantation.METHODS This cost-effectiveness analysis was based on historical cohort data obtained between 2000 and 2004 and involved 2,022 patients treated with cyclosporine or tacrolimus, matched 1:1 for gender, age, and type and year of transplantation. Graft survival and the direct costs of medical care obtained from the National Health System (SUS) databases were used as outcome results.RESULTS Most of the patients were women, with a mean age of 36.6 years. The most frequent diagnosis of chronic renal failure was glomerulonephritis/nephritis (27.7%). In five years, the tacrolimus group had an average life expectancy gain of 3.96 years at an annual cost of R78,360.57 compared with the cyclosporine group with a gain of 4.05 years and an annual cost of R61,350.44.CONCLUSIONS After matching, the study indicated better survival of patients treated with regimens using tacrolimus. However, regimens containing cyclosporine were more cost-effective.